A combined APT and SANS investigation of α′ phase precipitation in neutron-irradiated model FeCrAl alloys. (1st May 2017) - Briggs, Samuel A.; Edmondson, Philip D.; Littrell, Kenneth C.; Yamamoto, Yukinori; Howard, Richard H.; Daily, Charles R.; Terrani, Kurt A.; Sridharan, Kumar; Field, Kevin G.
Abstract: FeCrAl alloys are currently under consideration for accident-tolerant fuel cladding applications in light water reactors owing to their superior high-temperature oxidation and corrosion resistance compared to the Zr-based alloys currently employed. However, their performance could be limited by precipitation of a Cr-rich α ′ phase that tends to embrittle high-Cr ferritic Fe-based alloys. In this study, four FeCrAl model alloys with 10–18 at.% Cr and 5.8–9.3 at.% Al were neutron-irradiated to nominal damage doses up to 7.0 displacements per atom at a target temperature of 320 °C. Small angle neutron scattering techniques were coupled with atom probe tomography to assess the composition and morphology of the resulting α ′ precipitates. It was demonstrated that Al additions partially destabilize the α ′ phase, generally resulting in precipitates with lower Cr contents when compared with binary Fe-Cr systems. The precipitate morphology evolution with dose exhibited a transient coarsening regime akin to previously observed behavior in aged Fe-Cr alloys. Similar behavior to predictions of the LSW/UOKV models suggests that α ′ precipitation in irradiated FeCrAl is a diffusion-limited process with coarsening mechanisms similar to those in thermally aged high-Cr ferritic alloys. Graphical abstract: Image 1